Transformation of Cellulose via Two-Step Carbonization to Conducting Carbonaceous Particles and Their Outstanding Electrorheological Performance - Plachy, Tomas; Kutalkova, Erika; Skoda, David; Holcapkova, Pavlina (International journal of molecular sciences, 2022)
In this study, cellulose was carbonized in two-steps using hydrothermal and thermal carbonization in sequence, leading to a novel carbonaceous material prepared from a renewable source using a sustainable method without any chemicals and, moreover, giving high yields after a treatment at 600 °C in an inert atmosphere. During this treatment, cellulose was transformed to uniform microspheres with increased specific surface area and, more importantly, conductivity increased by about 7 orders of magnitude. The successful transition of cellulose to conducting carbonaceous microspheres was confirmed through SEM, FTIR, X-ray diffraction and Raman spectroscopy. Prepared samples were further used as a dispersed phase in electrorheological fluids, exhibiting outstanding electrorheological effects with yield stress over 100 Pa at an electric field strength 1.5 kV mm-1 and a particle concentration of only 5 wt%, significantly overcoming recent state-of-the-art findings. Impedance spectroscopy analysis showed clear interfacial polarization of this ER fluid with high dielectric relaxation strength and short relaxation time, which corresponded to increased conductivity of the particles when compared to pure cellulose. These novel carbonaceous particles prepared from renewable cellulose have further potential to be utilized in many other applications that demand conducting carbonaceous structures with high specific surface area (adsorption, catalyst, filtration, energy storage).
Keywords: elektrická vodivost; celulosa; electrorheology; Microspheres; mikrosféry; suspension; cellulose; adsorpce; X-Ray Diffraction; Electric Conductivity; conducting; renewable; difrakce rentgenového záření; Cellulose; Adsorption; carbonization